First report of natural infestation by Ostertagia ostertagi in water buffalo in Argentina: First report of natural infestation by Ostertagia ostertagi in water buffalo in Argentina (Veterinary Science, 2026)
Gastrointestinal nematodes (GINs) infestations are one of the main health problems in extensive production systems, causing clinical symptoms such as poor body condition, diarrhoea, anaemia, oedema and, in severe cases, mortality. In Argentina, the information available on helminth fauna in buffalo is scarce and limited to reports from slaughterhouses indicating the presence of Haemonchus spp. and Trichostrongylus spp. In September 2025, an outbreak of mortality (5,5%) associated with anaemia was investigated in a herd of approximately 450 buffalo between one and a half and two years old in Salta. The digestive tract of a necropsied animal was processed following standardised protocols, and Haemonchus spp. and Ostertagia ostertagi were identified. This finding constitutes the first formal record of O. ostertagi in buffalo in Argentina, probably acquired at the establishment of origin in Entre Ríos. The results suggest that buffalo may act as reservoirs of GINs of sanitary importance for cattle, highlighting the need to further investigate their epidemiology and productive relevance